English Students’ Satisfaction With Online Learning At Class - Sindi Sanora (Teaching English and Language Learning English Journal, 2021)
Students’ satisfaction is a condition where students can achieve what students want and feel satisfied. This research was done to find out students satisfaction with online learning at class This research is a qualitative research. Researcher used questionnaire as the instruments in collecting data. They were distributed to 60 students at class. There are six types of satisfaction analyzed by researchers, namely: Language Learning Potential, Learner Fit, Meaning Focus, Authenticity, Positive Impact and practicality. After analyzing the indicators, the result of the study show that students’ satisfaction with online learning is in satisfied classification with the highest options percentage (49%).Keywords: Students’ Satisfaction, Online Learning